Association of risk of suicide attempts with methylphenidate treatment - Man, Kenneth K.C.; Coghill, David; Chan, Esther W.; Lau, Wallis C.Y.; Hollis, Chris; Liddle, Elizabeth; Banaschewski, Tobias; McCarthy, Suzanne; Neubert, Antje; Sayal, Kapil; Ip, Patrick; Schuemie, Martijn J.; et al. (American Medical Association, 2017)
IMPORTANCE Patients with attention-deficit/hyperactivity disorder (ADHD) are at an increased risk of attempting suicide. Stimulants, such as methylphenidate hydrochloride, are the most common treatment for ADHD, but the association between their therapeutic use and suicide is unclear.